Coronary heart disease risk factors in middle-aged former top-level athletes - Pihl, E.; Jurimae, T.; Kaasik, T. (Scandinavian Journal of Medicine & Science in Sports, 1998)
A cross-sectional study was conducted to determine the impact of previous athleticism on coronary heart disease (CHD) risk factors in 168 middle-aged men and 147 middle-aged women in Estonia. Participants were divided into four groups: physically active ex-athletes (AA), sedentary ex-athletes (SA), recreational exercisers (RE), and non-exercisers (NE). The Sharkey's questionnaire was applied to determine the CHD risk factors, health habits, medical, safety, personal, psychological and women's risk factors scores. Anthropometric characteristics, resting systolic and diastolic blood pressure values (SBP, DBP), and physical working capacity (PWC170) were measured. Concentrations of total cholesterol (CHOL), high-density lipoprotein cholesterol (HDL-C), triacylglycerols (TG), and glucose were determined. Low-density lipoprotein cholesterol (LDL-C) and HDL-C/CHOL ratio were computed. From the questionnaire results, significant differences in CHD risk scores in both sex groups in favour of AA and RE were found. DBP in men was significantly higher in SA, and SBP in women was significantly higher in NE in comparison with other groups. PWC170 and PWC170/kg was highest in AA and lowest in NE in both sex groups. There were no significant differences for blood biochemical parameters between women's groups. In men, AA had a lower CHOL level in comparison with SA and NE, and lower concentrations of TG and LDL-C than other groups. AA and RE had a higher HDL-C concentration and HDL-C/CHOL ratio in comparison with the other groups. In conclusion, differences in CHD risk factors were related to current physical activity, and were more expressed in men than in women.